Developing the kiosk application system : a model of batik origin spatial knowledge display / Faridah Ahmat - Ahmat, Faridah (2006)
This research project is about constructing the Batik Origin Spatial Knowledge Display which will be uses for the kiosk application system. It will become an alternative way to display the information for the batik artifacts. Hence, the research also provided a knowledge sharing on batik with the museum visitors, prior to the gallery walkthrough. The objectives of this research project are to identify the data requirements needed for spatial knowledge display for the batik origin, to identify the chronological and historical fact for batik influence trail and to design the spatial information knowledge displays for the batik origin. Main data collection for this research is from the historical books on batik. From this source, the researcher gathered the historical and spatial information on batik origin. Then, the interviewed conducted with the batik expert to confirm and add some new information. After perform the documentation analysis, the researcher has identified the chronological and historical facts for the batik origin and it is presented by using the batik influence trail. Besides that, the research also comes out with the spatial information for the batik origin that will be used in developing the batik origin spatial knowledge display. Meanwhile, this research will refer to the batik knowledge mapping technique to present the spatial information for the batik origin on the digitized map. As a conclusion, the researcher found that this research project is beneficial since it can be used as a medium to share and manage knowledge on batik origin effectively.